Board Structure and Corporate Performance: A Causal Analysis of Select Indian Companies - Kakkar, Diksha; Kamboj, Garima (Prabandhan: Indian Journal of Management, 2011)
Corporate governance is one of the major issues emerging in the capital market. It deals with the agency problem. All firms face agency problems, and in the process of running a growing concern, develop measures to control them. Good corporate governance induces the board and management to work for the better interests of the shareholders. A lot of stress has been given on maintaining high ethical standards, thinking beyond the business, observing transparency for shareholders, bringing independent judgement and accountability from directors. Research shows that implementing best governance practices leads to hike in revenues and positive impact on performance of the companies. Board of directors are considered to be the crucial aspect of corporate governance. Various codes and reports have stressed on the independence of board of directors to bring efficiency in the business operations. Thus, the paper examines the impact of board size and their independence on the corporate performance, taking both book and market value performance measures. The sample of top 100 companies listed on S&P CNX 500 on the basis of market capitalization has been considered. The data for the five years i.e. 2004-05 to 2008-09 has been taken from annual reports of the companies and PROWESS database. The correlation and OLS regression have been applied on the time series data to find the results. The results being controlled for number of variables i.e. size, leverage, beta, ownership, age and nature of chairman. It has been proved that board independence is positively related with all the performance variables, except return on assets, while board size has negative impact on performance measured through price-earning ratio and Tobin's q. Thus, it can be concluded that the current scenario has changed and firms are giving stress on independence of directors rather than having larger boards. Yet, the task of selecting truly independent directors still remains a challenge.